(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
In the article, there are sources about the establishment of the Mir Arab madrasa in Bukhara due to the need for religious personnel during the Soviet era, and in this case, the creation of an educational program in accordance with the Soviet policy within the framework of Moscow's requirements, and in such a difficult situation, the most suitable and knowledgeable personnel were attracted to the madrasa in Bukhara with the efforts of the Religious Control. and opinions are based on archival data.